Pengaruh Pelatihan dan Kebijakan MSDM Terhadap Penurunan Stres Kerja Karyawan di Industri Manufaktur - Dera Andani (GLOBAL SCIENTS PUBLISHER, 2026)
The manufacturing sector is characterized by high work demands and complex operational environments that can trigger employee work stress. Unmanaged stress negatively affects productivity, mental health, job satisfaction, and turnover rates. Prior literature indicates that employee training and Human Resource Management (HRM) policies serve as strategic interventions for stress mitigation. Training enhances employee competence and role clarity, while effective HRM policies create fairness, stability, and organizational support. This study adopts a quantitative survey method using a Likert-scale questionnaire distributed to manufacturing employees in Karawang, Indonesia. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to assess validity, reliability, and hypothesis testing. The empirical results show a significant effect of training on reducing work stress (coefficient = 0.412; p = 0.000) and a significant effect of HRM policies on stress reduction (coefficient = 0.398; p = 0.000). Simultaneously, both variables explain 62.4% of the variance in work stress reduction (R² = 0.624), while the remaining variance is influenced by other factors. These findings confirm that comprehensive HRM interventions are needed to manage stress in manufacturing settings. Training improves employee adaptability, while HRM policies strengthen work security and support systems.